Sole Propriesorship and Limited Liability Company Financial Liabilites To Creditors - Suwinto Johan; Ariawan (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The government has issued the Job Creation Law. In the Job Creation Law, micro and small businesses can establish a legal entity company. This company is called a sole proprietorship. The establishment of a sole proprietorship is still difficult to distinguish from establishing a limited liability company based on the Law of the Republic of Indonesia Number 40 of 2007. One thing that becomes the attention of stakeholders is the responsibility of sole proprietorships with limited liability. Stakeholders include creditors of financial institutions. This research uses a normative judicial method. This research object is aims to discuss the disadvantage of sole proprietorships compared to limited liability companies to creditors of financial institutions. The research result is find the differences between a sole proprietorship and a limited liability company. This research concludes that a sole proprietorship with limited liability is the same as that of a limited liability company to creditors of financial institutions. Shareholders are not responsible for ties to individual companies. The board of directors is not personally accountable for respective companies' obligations. A particular company is responsible for relations made on its behalf as a legal entity. Any responsibility includes a credit agreement between the company and a financial institution.